Pharmacogenetics of SSRIs and Sexual Dysfunction - Liana Osis; Jeffrey R. Bishop (MDPI AG, 2010)
Sexual dysfunction (SD) is a common and disconcerting side effect of selective serotonin reuptake inhibitors (SSRIs) that often influences a patient's desire to continue long-term antidepressant treatment. Studies specifically assessing changes in sexual well-being over time illustrate that the incidence of sexual side effects from SSRIs ranges from 20% to 70%, depending on the characteristics of the study sample assessed. Developing strategies to predict who may be at the highest risk for adverse changes in their sexual well-being is an important step in improving the quality of life and treatment of patients who require antidepressant therapy. Pharmacogenetic studies of SSRI-associated SD have identified associations between serotonin and glutamate system genes with aspects of SD. The results of studies investigating genetic variations in drug metabolism enzymes and their relationships to antidepressant-associated adverse effects have been mixed. Continued efforts to characterize the relationships between genetic markers and antidepressant outcomes, and to translate this knowledge to patient care, have the potential to significantly improve the empiric selection of antidepressant agents and to minimize the risk for intolerable side effects.